(NpOWESTI I RASSKAZY(B: [1885-1902] /s (N~ASTX (B12s - (NtOLSTOJ(B, (NlEW nIKOLAEWI^s ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1982)
(Nw TOM WKL@^ENY POWESTI I RASSKAZY l(B.(Nn(B. (NtOLSTOGO (B1885-1902 (NGODOW(B: "(NhOLSTOMER(B", "(NsMERTX iWANA iLXI^A(B", "(NkREJCEROWA SONATA(B", "(NhOZQIN I RABOTNIK(B", "(NoTEC sERGIJ(B" (NI DR(B.s
rus
Keywords: (NpOWESTI I RASSKAZYs